Synthesis of biodiesel from Jatropha curcas oil using waste eggshell and study of its fuel properties - Chavan S.B.; Kumbhar R.R.; Madhu D.; Singh B.; Sharma Y.C. (My University, 2025)
High purity calcium oxide (CaO) was prepared from eggshell and used as a catalyst for the production of biodiesel. Non-edible oil, Jatropha curcas was used as a feedstock for the synthesis of biodiesel. High purity calcium oxide (CaO) was obtained when the eggshell was subjected to calcination at 900°C for ∼2.5 h. Confirmation of the catalyst was carried out by X-ray diffraction, Fourier transform infrared spectrometry (FT-IR), and differential thermal and thermogravimetric analysis (DTA-TGA). The synthesized biodiesel was characterized using 1H NMR. Pure biodiesel was obtained in high yield by taking into account various parameters such as a proper methanol to oil molar ratio, reaction temperature and reaction time. Reusability of the catalyst was observed and the catalyst worked efficiently up to six times without significant loss of activity. Physical and chemical properties of biodiesel such as density, kinematic viscosity, cloud point, etc. were studied. © The Royal Society of Chemistry 2015.